(untitled) (Tzintzun, Revista de Estudios Históricos, 2024)
This paper reconstructs the beginnings of the Young Catholic Students (YCS) in the stablishments of the Brothers of the Christian Schools in Mexico between 1961-1963. Thus, in the first place, the beginnings of this specialized Catholic Action movement are narrated. Then a description is made of the guidelines under which the Lasallian YCS was carried out in Mexico, after which a recount is made of the strategies that were used to disseminate and support this activity. The text ends by exposing the first steps of the North Mexico district with the purpose of consolidating the Young Catholic Students in its territory.